“One Human Family” and Interfaith Greetings: President Prabowo’s Islamic Normativity vis a vis the Indonesia Ulema Council (MUI) Edict - Ryan Bianda (Muslim Politics Review, 2026)
This article examines how Islamic normativity is constructed and contested through interfaith greetings in President Prabowo Subianto’s address at the United Nations General Assembly and the 2024 Indonesian Ulema Council edict (fatwa) on relations with followers of other religions. Rather than treating interfaith greetings merely as polite formulas or as a simple halal-haram issue, the article analyzes them as symbolic practices located between state diplomacy and Islamic legal authority. Using a qualitative interpretive case-study design and directed qualitative content analysis, the study examines the official transcript of the presidential speech and the full text of the fatwa through four analytical categories: normative construction, rhetorical-diplomatic function, fatwa reasoning, and patterns of convergence and divergence. The findings show that Prabowo’s interfaith greetings and “one human family” rhetoric function as diplomatic speech acts that present Indonesia as a plural Muslim-majority state committed to peace, recognition, and global fraternity. By contrast, the fatwa constructs certain interfaith greetings as potentially devotional utterances that require legal-theological evaluation to protect Islamic monotheism (tawḥīd), worship boundaries, and confessional clarity. Together, the two texts reveal a dual-track configuration of Islamic normativity in which state diplomacy and fatwa authority share an ethical horizon of coexistence but diverge on the permissible symbolic forms of interreligious engagement.